2003
DOI: 10.1109/lpt.2003.809298
|View full text |Cite
|
Sign up to set email alerts
|

All-optical bit-error monitoring system using cascaded inverted wavelength converter and optical NOR gate

Abstract: A novel all-optical bit-error monitoring system is demonstrated by cascading two all-optical logic gates: an inverted wavelength converter and an optical NOR gate which are realized using injection-locked laser diodes operating at different thresholds. Real-time optical monitoring signal is generated which indicates the positions and duration of both bit and burst errors in 10-Gb/s nonreturn-to-zero signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 6 publications
0
29
0
3
Order By: Relevance
“…The key problem in the all-optical bit-error monitoring is the generation of the error bit indicating signal (EBIS) in the optical domain without optical-to-electrical and electrical-to-optical conversion. Chan et al demonstrated a novel all-optical bit-error indicating scheme at 10 Gb/s using two cascaded injection-locked Fabry-Pérot laser diodes (FP-LDs) as all-optical logic NOT and NOR gate, respectively [4]. Chan's research is revelatory for the future development of the all-optical bit-error monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The key problem in the all-optical bit-error monitoring is the generation of the error bit indicating signal (EBIS) in the optical domain without optical-to-electrical and electrical-to-optical conversion. Chan et al demonstrated a novel all-optical bit-error indicating scheme at 10 Gb/s using two cascaded injection-locked Fabry-Pérot laser diodes (FP-LDs) as all-optical logic NOT and NOR gate, respectively [4]. Chan's research is revelatory for the future development of the all-optical bit-error monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Optical logic is essential for signal processing in the optical switching application, such as bit error monitoring [77], bit pattern recognition [78], label-swapping [79], optical packet address and payload separation [80], and optical routing decision [81]. Optical logic gates like AND, NOT, OR, XOR, NAND, and XNOR functions have been realized based on the nonlinearities of the SOA, such as XGM, XPM, XPolM, and FWM.…”
Section: Optical Logicmentioning
confidence: 99%
“…In fact high speed communication and processing are key features for future ultra-fast transmission and computing systems, within scenarios ranging from widearea backbone networks to inter-chip interconnection networks. Nevertheless, few examples of the simple cascade of two logic gates have been demonstrated Chan et al, 2003), while the design and the implementation of more complex digital circuits involving cascades of several logic functions have not been addressed yet. Here it is presented an implementation of the combinatorial circuit for a 22 photonic node architecture, where all the forwarding functions (label recognition and processing, contention detection and resolution, switch control, switching, and regeneration) are optically performed by exploiting integrable solutions .…”
Section: Photonic Combinatorial Circuit For Contention Management In mentioning
confidence: 99%